A systematic review of seroma formation following drain-free mastectomy. Issue 4 (April 2021) - De Rooij, L.; Bosmans, J.W.A.M.; van Kuijk, S.M.J.; Vissers, Y.L.J.; Beets, G.L.; van Bastelaar, J.
Abstract: Background: Seroma is a common complication after mastectomy. The aim of this review is to elucidate whether closed suction drainage can safely be omitted in patients undergoing mastectomy when assessing seroma formation and its complications. The second aim is to assess the influence of flap fixation on seroma related complications, as there is existing evidence showing that combining mastectomy with flap fixation may make the use of drainage systems obsolete. Search & selection: A review of the literature was performed and articles that compared mastectomy with drainage and mastectomy without drainage were selected. Due to the small number of eligible studies, no selection based on whether flap fixation was performed was possible. If outcome was described in terms of seroma formation or seroma related complications, papers were eligible for inclusion. Studies older than 20 years, animal studies, studies not written in English and studies with male patients were excluded. Results: A total of eight articles were eligible for inclusion. Four prospective studies and four retrospective studies were included. In four studies, flap fixation was performed. Frequency of seroma formation as well as seroma that required intervention was reported. The included studies demonstrated that omitting closed suction drainage does not lead to a higher incidence of seroma formation in patients undergoing mastectomy. Conclusion: Despite substantial heterogeneity, there is evidence that drainage can safely be omitted without exacerbating seroma formation and its complications. A well-powered, randomized controlled trial evaluating the effect of drainage omission on seroma formation, with or without flap fixation, is needed.